Labour-market integration of immigrants in OECD-countries: What explanations fit the data? - Andreas Bergh (European Centre for International Political Economy (ECIPE), 2013)
Using two different measures of immigrant labour-market integration (the ratio between immigrant unemployment to native unemployment, and the ratio of employment rate among natives and immigrants) this paper tests six suggested explanations of why immigrants are less likely than natives to be working in most OECD-countries: Intolerance, the education of immigrants, welfare state generosity, employment protection laws, union power and the share of immigrants in the population. Using bivariate and multivariate analysis, two significant patterns are found. First, welfare state generosity keeps immigrants away from the labour force. Second, given that immigrants enter the labour force, collective bargaining agreements explain immigrant unemployment. No other factors are statistically significant in cross-country regressions.
Keywords: 330; Arbeitsmarktintegration; Migranten; Arbeitslosigkeit; Vergleich; Öffentliche Sozialleistungen; Tarifverhandlungen; Multivariate Analyse; OECD-Staaten